PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) PADA IPAS MATERI TUMBUHAN BAGI PESERTA DIDIK TUNARUNGU DI SLB NEGERI SERDANG BEDAGAI SUMATERA UTARA - Beta Rapita Silalahi; Dalimawaty Kadir; Maya Meili; Fakhira Ulfa; Anatasya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of the Project Based Learning (PjBL) model in teaching plant recognition to hearing-impaired students at SLB Negeri Serdang Bedagai. The research was conducted following observation and teaching practice activities in a special education setting, where students were grouped according to their type of disability. Learning activities were carried out in the classroom using visual-based instructional media, including plant images and printed puzzle projects. Data collection techniques involved classroom observation and documentation of student learning activities. The findings indicate that the implementation of Project Based Learning encouraged active student participation, facilitated better understanding of plant concepts, and increased students’ learning motivation. Hands-on project activities supported by visual media were found to be highly suitable for the learning characteristics of hearing-impaired students. Therefore, Project Based Learning can be considered an effective instructional model for science learning in special schools.